Amanita ochroterrea and Amanita brunneiphylla (Basidiomycota), one species or two? - Davison, Elaine (Western Australia, Department of Conservation and Land Management, 2011)
Amanita ochroterrea (Gentilli) Bas and A. brunneiphylla O.K.Miller are robust, macroscopically similar mushrooms described from the southwest of Western Australia. According to the protologue of A. brunneiphylla, the main difference between them is the presence (in A. ochroterrea) or absence (in A. brunneiphylla) of clamp connections. However in the current study abundant clamp connections have been observed in the holotype and paratypes of A. brunneiphylla. As other microscopic characters are indistinguishable, A. brunneiphylla is synonymised with A. ochroterrea, and an expanded description presented.